A review of retroperitoneal liposarcoma genomics. (June 2020) - Tyler, Robert; Wanigasooriya, Kasun; Taniere, Philippe; Almond, Max; Ford, Samuel; Desai, Anant; Beggs, Andrew
Highlights: This represents the first retroperitoneal specific review of liposarcoma genomics. Liposarcoma's molecular landscape is becoming better understood. There is more interest in genomic drivers outside the classic 12q13-15 amplicon. The Hippo pathway is likely oncogenic in myxoid liposarcoma. CRISPR and new sequencing technologies are anticipated to identify new targets. Abstract: Retroperitoneal liposarcomas are rare tumours that carry a poorer prognosis than their extremity counterparts. Within their subtypes – well differentiated (WDL), dedifferentiated (DDL), myxoid (MLS) and pleomorphic (PLS) - they exhibit a diverse genomic landscape. With recent advances in next generation sequencing, the number of studies exploring this have greatly increased. The recent literature has deepened our understanding of the hallmark MDM2 / CDK4 amplification in WDL/DDL and addressed concerns about toxicity and resistance when targeting this. The FUS-DDIT3 fusion gene remains the primary focus of interest in MLS with additional potential targets described. Whole genome sequencing has driven identification of novel genes and pathways implicated in WDL/DDL outside of the classic 12q13-15 amplicon. Due to their rarity; anatomical location and histologic subtype are infrequently mentioned when reporting the results of these studies. Reports can include non-adipogenic or extremity tumours, making it difficult to draw specific retroperitoneal conclusions. This narrative review aims to provide a summary of retroperitoneal liposarcoma genomics and the implications for therapeutic targeting.